The Effect of Halal Price Label Product Quality and Halal Knowledge on Muslim Consumer Preference in Purchasing Scarlett Whitening Body Lotion: (Case Study of Santri Students in Bantul Regency) - Azizah, Alifia Fitri Nur; Yunadi, Ahmad; Salam, Abdul; Ismiati, Baiq (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study aims to determine the effect of halal labels, prices, product quality and halal knowledge on Muslim consumer preferences in purchasing scarlett whitening body lotion. This research is quantitative research, which is taken from known samples. The population in this study were students of Bantul Regency. The sampling technique used porposive sampling to find a sample of 100 respondents. The type of data used is primary data where this data is in the form of a questionnaire. Data analysis techniques using SPSS. This research will produce partial and simultaneous tests. The results showed that the halal label variable did not affect the decision to purchase scarlett whitening body lotion. The price variable influences the decision to purchase scarlett whitening body lotion. Product quality variables influence the decision to purchase scarlett whitening body lotion. The halal knowlwdge variable influences the decision to purchase scarlett whitening body lotion. So it can be concluded that there is a simultaneous influence of the variable halal label, price, product quality, and halal knowledge on the decision to buy scarlett whitening body lotion.